2006
DOI: 10.1143/jjap.45.6043
|View full text |Cite
|
Sign up to set email alerts
|

Density Control of Carbon Nanotubes through the Thickness of Fe/Al Multilayer Catalyst

Abstract: Isolated hydrogen and muonium in crystalline silicon have been studied by the path-integral Monte Carlo method, using a parametrized Si-H interaction derived from earlier ab initio calculations. Hydrogen and deuterium are found to be stable at the bond-centre (BC) site, but this position is metastable for muonium. Average values of the kinetic and potential energy of the defects are compared with those expected for the hydrogen-like impurities within a harmonic approximation. The backwards relaxation of the Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…In addition to the majority of studies that have focused on the Fe/Al 2 O 3 catalytic system, others have focused on efforts to engineer the catalyst support material (replacing Al 2 O 3 ) either to discover routes toward optimal material combinations for CNT growth, 28 or to increase the functionality of as-grown CNT structures. This has included metal catalysts deposited on a number of materials including TiN, [29][30][31] Ta, 32,33 Al, [34][35][36] Ti, 37 Ir, 38 MgO, 39 CoSi 2 , 40,41 stainless steels, 42,43 copper foils, 44 and Si 45,46 among others. Although aligned CNT array growth is observed in most of these studies, these materials characteristically support the growth of lower-quality CNTs having shorter lengths and lower CNT densities in the arrays, thus emphasizing the ideal nature of the Fe/Al 2 O 3 catalyst system.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the majority of studies that have focused on the Fe/Al 2 O 3 catalytic system, others have focused on efforts to engineer the catalyst support material (replacing Al 2 O 3 ) either to discover routes toward optimal material combinations for CNT growth, 28 or to increase the functionality of as-grown CNT structures. This has included metal catalysts deposited on a number of materials including TiN, [29][30][31] Ta, 32,33 Al, [34][35][36] Ti, 37 Ir, 38 MgO, 39 CoSi 2 , 40,41 stainless steels, 42,43 copper foils, 44 and Si 45,46 among others. Although aligned CNT array growth is observed in most of these studies, these materials characteristically support the growth of lower-quality CNTs having shorter lengths and lower CNT densities in the arrays, thus emphasizing the ideal nature of the Fe/Al 2 O 3 catalyst system.…”
Section: Introductionmentioning
confidence: 99%
“…Reports had shown that carbon nanotube (CNT)-based field emitter exhibits excellent field emission properties due to its superior thermal and electrical characteristic [ 11 ]. However, the wire number density of as-grown CNTs is usually as high as 10 10 CNTs/cm 2 [ 12 ]. Such a dense CNT structure would suffer from the so-called electrostatic screening effect provoked by the proximity of neighboring wires which results in limited field emission performance.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there have been numerous studies that report changes in the carbon nanotube growth (e.g., nanotube structure and nucleation density) brought about by the inclusion of catalyst support materials or metallic underlayers (e.g., Cr, Ir, W, Ta, and Ti), positioned between the bulk substrate (usually Si) and catalytic nanoparticles. Interestingly, aluminum (with a native surface oxide) (Al/Al 2 O 3 ) or alumina (Al 2 O 3 ) films deposited by high-vacuum processes or from solution have been particularly effective at promoting the growth of carbon nanotubes on substrates such as Si, SiO 2 or metals (e.g., Au, Ag, W, NiCr, steel) for a range of catalytic materials (e.g., Co, Ni, Fe). , Various explanations have been offered to account for the remarkable efficacy of Al/Al 2 O 3 in promoting carbon nanotube growth. Notable suggestions are that the Al/Al 2 O 3 acts as a diffusion barrier preventing catalyst from being eliminated to the substrate ,, or that the key property of the oxidized aluminum is its thickness, ,,,, morphology, ,,,, reactivity, ,,,, or surface energy/wettability. , These studies indicate that the action of the buffer layer extends beyond topographic effects alone. However, since the effect of surface morphology has not been investigated in isolation, the influence of underlayers of both different chemical composition and structure on carbon nanotube growth does not allow topographic effects to be readily ascertained.…”
Section: Introductionmentioning
confidence: 99%